Altered interhemispheric resting‐state functional connectivity in young male smokers. (5th May 2017) - Yu, Dahua; Yuan, Kai; Bi, Yanzhi; Luo, Lin; Zhai, Jinquan; Liu, Bo; Li, Yangding; Cheng, Jiadong; Guan, Yanyan; Xue, Ting; Bu, Limei; Su, Shaoping; et al.
Abstract: With the help of advanced neuroimaging approaches, previous studies revealed structural and functional brain changes in smokers compared with healthy non‐smokers. Homotopic resting‐state functional connectivity between the corresponding regions in cerebral hemispheres may help us to deduce the changes of functional coordination in the whole brain of young male smokers. Functional homotopy reflects an essential aspect of brain function and communication between the left and right cerebral hemispheres, which is important for the integrity of brain function. However, few studies used voxel mirrored homotopic connectivity (VMHC) method to investigate the changes of homotopic connectivity in young male smokers. Twenty‐seven young male smokers and 27 matched healthy male non‐smokers were recruited in our study. Compared with healthy male non‐smokers, young male smokers showed decreased VMHC values in the insula and putamen, and increased VMHC values in the prefrontal cortex. Correlation analysis demonstrated that there were significant positive correlations between the average VMHC values of the prefrontal cortex and pack‐years in young male smokers. In addition, significant negative correlation was found between the average VMHC values in the insula and pack‐years. Our results revealed the disrupted homotopic resting‐state functional connectivity in young male smokers. The novel findings may extend our understanding of smoking. Abstract : Compared with healthy male non‐smokers, young male smokers showed decreased voxel mirrored homotopic voxel (VMHC) values in the insula and putamen, and increased VMHC values in the prefrontal cortex. Correlation analysis demonstrated that there were significant correlations between pack‐years and the average VMHC values of the prefrontal cortex and insula. Our results revealed the disrupted homotopic resting‐state functional connectivity in young male smokers, which may extend our understanding of smoking.